Role of MacroH2A2 in the glioblastoma stem cell epigenome. (September 2019) - Nikolic, A; Ellestad, K; Johnston, M; Dirks, PB; Zemp, FJ; Gafiuk, C; Mahoney, DJ; Gallo, M
Abstract : Glioblastoma is the most common primary malignant brain tumour in adults, and remains uniformly lethal. These tumours contain a subpopulation of glioblastoma stem cells (GSCs) that drive tumour recurrence and drug resistance. We find that MacroH2A2 is a histone variant that can stratify glioblastoma patients, with higher levels of this histone variant associated with better patient prognosis. Knockdown of macroH2A2 in GSCs is associated with increased self-renewal and an increased expression of stemness genes by RNA-seq. Our preliminary results suggest that macroH2A2 is a novel biomarker for glioblastoma and that macroH2A2 loss is a marker of GSC stemness and a poor prognostic marker in glioblastoma. This work identifies loss of macroH2A2 as a feature of GSCs and provides a framework for therapeutic modulation of this histone variant. LEARNING OBJECTIVES: This presentation will enable the learner to: 1. Explain the role of epigenetics in glioblastoma pathophysiology